Drinking to reach the top: Young adults' drinking patterns as a predictor of status within natural drinking groups - Dumas, T.; Graham, Kathryn; Bernards, S.; Wells, S. (Pergamon, 2014)
In this study we examined associations between young adults' drinking patterns and social status within their natural drinking groups (NDGs) and assessed gender differences in these relationships. Same-sex NDGs (n = 104) on route to a bar district were recruited and completed a peer-nominated measure of within-NDG status.In a follow-up online survey, participants (n = 293; 174 men and 119 women) reported their usual drinking pattern within the past year. Hierarchical Linear Modeling revealed that men who engaged in more frequent heavy episodic drinking (HED) (both for 5+ and 8+ drinks in one sitting) and women who drank more frequently were nominated as occupying higher-status positions within their NDGs compared to their peers who drank less. Further, for both men andwomen, drinkingmore than one's peers during one's heaviest drinking occasion in the past year was also associated with higher within-NDG status. These findings suggest that highersocial status is associated with riskier drinking patterns and have important implications for prevention programming.